Worsening of cluster headache pattern associated with glioblastoma multiforme: a case report - Oliveira, Bruna Maria Cristino; Bossa, Beatriz Bagatim; Rodrigues, Jean Carlos Bofi; Cortez, Bruna Bobato; Thompson, Marla Tahana; Fenato, Luiz Henrique Parra; Galo, Camila Stringuetta; Scheidt, Joao Felipe Hermamm Costa; Silva, Aline Vitali Da (Headache Medicine, 2024)
INTRODUCTION: Cluster headache is the most common trigeminal autonomic cephalalgia, characterized by intense, unilateral headache accompanied by autonomic symptoms1. The recommended investigation includes Brain Magnetic Resonance Imaging (MRI), which is expected to show no abnormalities. On the other hand, glioblastoma multiforme (GBM) is the most common and aggressive primary tumor in adults2, with headache being an unusual presentation. OBJECTIVE: To present an unusual case of worsening cluster headache associated with the onset of GBM. CASE REPORT: An 88-year-old male patient attended the headache clinic at PUC-PR, Londrina-PR, complaining of very severe, right-sided, pulsating headaches, associated with facial flushing, tearing, and ipsilateral rhinorrhea, lasting between 15-20 minutes and occurring 2-3 times a day. The events did not improve with common analgesics. He had been experiencing this pain for over 20 years; however, in the past year, it had become more frequent and unremitting. His neurological examination and fundoscopy examination were unremarkable. A brain MRI was requested, and an occipital anesthetic block was performed. Before the MRI was performed, the patient suffered a fall with head trauma and began to exhibit mental confusion. The MRI showed an expansive lesion located in the right occipito-temporal region with invasion of the splenium of the corpus callosum and water diffusion restriction measuring 4.5x2.7x4.0 cm, suggestive of GBM. The same examination also identified a subdural hematoma with a thickness of 2 cm which was drained. The family chose not to address the tumor lesion. After 4 months, the patient returned to the headache clinic, with his daughter reporting that since the anesthetic block, the patient had not experienced any headache episodes. Finally, 8 months after the initial consultation, the patient died. CONCLUSION: Imaging studies are essential in trigeminal autonomic cephalalgias and should not be neglected despite long disease evolution and favorable response to implemented therapy.